Consumer Economic Behavior of Generation Z: The Role of Promotion, Lifestyle, and Store Atmosphere on Repurchase Intention Mediated by Customer Satisfaction at Starbucks in Bali - Jaya, I Gst Ngurah Bagus Putra; Suardana, Ida Bagus Raka (Yayasan Riset dan Pengembangan Intelektual, 2025)
The coffee shop industry in Indonesia is growing rapidly, especially among Generation Z who have made coffee a part of their lifestyle. Starbucks faces intense competition and needs to understand the factors that influence repurchase intentions, such as promotions, lifestyle, and store atmosphere. This study aims to provide a comprehensive insight into the factors that influence repurchase decisions among Generation Z, focusing on aspects of promotion, lifestyle, and store atmosphere, and how customer satisfaction can mediate these influences. The research design used in this study is a quantitative approach in the form of an associative causal approach. The results showed that promotion, lifestyle, and store atmosphere have a positive and significant effect on customer satisfaction at Starbuck in Bali Province. Promotion, lifestyle, store atmosphere, and customer satisfaction have a positive and significant effect on repurchase intentions at Starbuck in Bali Province. Customer satisfaction is able to mediate the effect of promotion, lifestyle, and store atmosphere on repurchase intentions at Starbuck in Bali Province. This means that an increase in promotion, lifestyle, and store atmosphere will increase customer satisfaction and will also increase consumer repurchase intentions with products at Starbuck in Bali Province.